The Effect of Solution Treatment Temperature and Quenching Media Variation in Heat Treatment Process Cu-Zn-Al Shape Memory Alloys on Shape Memory Effect and Microstructures - Jatimurti, Wikan; Gayatri, Monica; Ramadhani, Mavindra (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
Shape memory alloys (SMAs) are metal alloys with a reversible ability to recover their shape at a certain temperature after being deformed. This ability referred to as Shape Memory Effect (SME). The application of SMAs such as Ni-Ti and Cu-Zn-Al alloys usually used on automotive, biomedical, etc. The commonly used SMA is Ni-Ti because of its superior SME properties than Cu-Zn-Al, even though the price is quite higher. The SME of Cu-Zn-Al might be improved by increasing the presence of the martensite phase in its microstructure by heat treatment. The heat treatment process given to Cu-21Zn-5Al alloy is a homogenizing, annealing, solution treatment process and quenched with brine solution and dry ice. The heat-treated alloys then undergo several examination trough hardness tests, X-Ray Diffraction, metallography, SME test, and Differential Scanning Calorimetry to determine the SME and microstructure of Cu-21Zn-5Al. From the test results, the specimen with temperature treatment solution of 850oC and quenched by brine solution had the highest SME value by 36.67%. All of the microstructure contained α, β, (martensite) and γ phases.